2017
DOI: 10.1016/j.bjm.2016.09.015
|View full text |Cite
|
Sign up to set email alerts
|

Modified Carba NP test for the detection of carbapenemase production in gram-negative rods: optimized handling of multiple samples

Abstract: The modified Carba NP test presented here may be a valuable tool for laboratories interested in investigating a large number of carbapenemase-producing bacteria in a less-costly way. The test was evaluated against 48 carbapenemase-producing and carbapenemase-non-producing gram-negative bacteria. No false–positive results were obtained, but false-negative results were observed with OXA-23- and GES-carbapenemase-producing isolates. Aeromonas sp. are not testable by Modified Carba NP.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 14 publications
1
5
1
Order By: Relevance
“…38 Similar reports of low sensitivity for the Carba NP test have been reported. 21,22,39 In contrast to the Carba NP test that failed to detect six isolates that were genotypically confirmed to carry at least one carbapenemase gene, the present study revealed that MHT was more sensitive than the Carba NP test, based on failure of MHT to detect only five isolates that were genotypically confirmed to harbor at least one carbapenemase gene.…”
Section: Discussioncontrasting
confidence: 83%
See 2 more Smart Citations
“…38 Similar reports of low sensitivity for the Carba NP test have been reported. 21,22,39 In contrast to the Carba NP test that failed to detect six isolates that were genotypically confirmed to carry at least one carbapenemase gene, the present study revealed that MHT was more sensitive than the Carba NP test, based on failure of MHT to detect only five isolates that were genotypically confirmed to harbor at least one carbapenemase gene.…”
Section: Discussioncontrasting
confidence: 83%
“…Early and rapid detection of these isolates is crucial for initiating effective therapeutic options as early as possible in order to achieve desirable outcomes, especially for serious infections and to prevent the spread of these XDR isolates, 21,22 based on that, the current study used three phenotypic methods for detection of carbapenemase production among CRKP clinical isolates: (i) MHT (ii), Carb NP test, and (iii) CDST.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Species identification was determined primarily with an automated VITEK®2 AST-16 Gram-negative susceptibility card (bioMérieux, Marcy-l’Étoile, France) and confirmed by matrix-assisted laser desorption ionisation-time of flight mass spectrometry (MALDI-TOF MS). Investigation of carbapenemase production in the routine hospital laboratory procedure using the Modified Hodge Test (MHT) [ 37 ] and Carba NP test [ 38 ] showed that EBSI041 was resistant to carbapenems. We tested EBSI041 for carbapenems-resistant genes and confirmed that it carried bla OXA-48 and bla KPC-2 .…”
Section: Methodsmentioning
confidence: 99%
“…A study by Hamid El Abd et al concluded the sensitivity and specificity to be 100% for the detection of both KPC and MBL producers. Another study carried out by Campana et al reported 73.1% sensitivity and 100% specificity. These studies support the current study, concluding 91.7% sensitivity and 96.7% specificity.…”
Section: Discussionmentioning
confidence: 99%